(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Dengue infection recently. An alarming surge in dengue among Bangladeshi children has created an enormous burden in morbidity and mortality. This study aimed to document the profile, outcome and associated factors of clinical outcomes of dengue patients admitted to the PICU of a tertiary-level hospital in Chattogram, Bangladesh, during the 2022 outbreak. Materials and methods: This prospective observational study was performed among children with dengue infection who were admitted to the PICU of Chittagong Medical College Hospital from 1st August 2022 to 31st December 2022. Clinical features, laboratory parameters and outcome of transfer from ICU to ward or death were studied and described. Results: The patients’ Median (IQR) age was 5.0 (1.5-10.5). Most patients were urban dwellers (69.6%); 56.5% were male. Common findings during admission were persistent vomiting (60.9%), lethargy (52.2%), positive tourniquet test (78.3%), and hypotension (69.6%). Dengue shock syndrome and dengue hemorrhagic fever were diagnosed in 56.4% and 30.5% of the patients. The median length of stay in the PICU was 4 (3-6) days. The overall outcome revealed that 78.5% of patients were improved and discharged, and 21.5% died in the PICU. In univariate analysis, factors associated with PICU mortality were younger age, altered level of consciousness, lethargy, shock and prolonged CRT at admission (p<0.05). All of the deceased cases had dengue shock syndrome. Conclusion: One out of every five PICU-admitted dengue cases expired. A multicenter study with a large sample size must have a clear picture of the predictors of poor outcomes. Chatt Maa Shi Hosp Med Coll J; Vol.23 (1); January 2024; Page 42-46